MYTHS, RITUALS AND RESTRICTIONS OF THE AFRICAN IRON INDUSTRY IN THE 18th CENTURY: THE CASE OF TAAVISA IN NSO’ GRASSFIELDS OF CAMEROON - Dzeawoni, Atlee (American International Journal of Social Science Research, 2021)
The peculiarity of the African iron industry is its cultural dimension; where in, symbolism was evident in virtually all the stages of the production chain. With the use of archival, secondary and oral sources, this paper investigated the Taavisa slag heap which revealed that smelting residue was cleared to create space for a royal cemetery and a hut constructed over the grave of Fon (king) Sanggu of Nso’ around 1750. Sanggu was probably the seventeenth Sovereign of the Nso’ Dynasty at Kovifem, who died while in refuge on the peripheries of his kingdom, subjected to Chamba and later Fulani raids. Taavisa was a retreat spot in several situations and developed into a rest palace for reigning Fons of Nso’. Given its strategic location, smelting, pre-forging and sanctity which emanated from iron works, this old iron working site became a place of honour and thus mutated into a shrine. Thus, multidimensional values attached to Taavisa account for Nso’ seizure of the area and subsequent expansion towards its southern boarder Fondoms (Kingdoms). A new element therefore adds to symbolisms attached to the African iron industry that is: a smelting site turned into a royal cemetery.